“A laugh a day keeps the failure away”: The role of self-enhancing humor and host country community embeddedness in career satisfaction of dual-earner expatriate couples - Nguyen, Anh; Andresen, Maike (Frontiers in Psychology, 2023)
For dual-earner expatriate couples (DEECs), it is particularly challenging to achieve career satisfaction after relocating to another country and the associated career transitions. While studies have addressed the strenuous career pathways of individuals in DEECs, the identification and empirical analysis of resources that may contribute to the attainment of career satisfaction remains a desideratum. This research investigates the impact of self-enhancing humor and community embeddedness on individual career satisfaction and the crossover effects of humor on that of the partners in DEECs. Using data from 109 DEECs in Europe and Actor-Partner Interdependent Model (APIM), the results show that embeddedness in one’s community mediated the relationship between humor and career satisfaction. The study also unfolded the crossover effects of humor within couples: Men’s humor promoted their female partner’s community embeddedness, which, in turn, promoted women’s career satisfaction. This study entails fruitful implications for future research on DEECs and practical recommendations for relevant stakeholders to facilitate the careers of DEECs.